Questioning the artistic dissertation: Barthesian and Gamsonian analysis of art creation research in Indonesia - Suranto, Joko; Sularso, Sularso (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2025)
This study examines the dissertation manuscript of art creation in the Doctoral Program of Art Creation, Institut Seni Indonesian (ISI) Surakarta, with the aim of revealing the construction of meaning and the problems of its authorship. This study combines Roland Barthes' semiotic theory and William Gamson's media framing devices in an integrative manner. Gamson's framing devices—including metaphors, slogans, exemplars, depictions, and visual images—are used to identify the dominant representational elements in the manuscript. Furthermore, Barthes' semiotic approach is applied to analyze the denotative and connotative meanings of these elements. The results of the study identified two main categories of meaning in the dissertation: reflective and substantial meaning. On the other hand, the study of the authorship problems found two main issues, namely the positioning strategy of the Nusantara Aesthetic concept as a strengthening of institutional identity, and the formatology of authorship that shows the tension between academic conventions and creative expression. This study concludes that the level of epistemological awareness of the author affects the scientific quality of the dissertation, and confirms that the dissertation of art creation has an inherent contribution to the artwork itself. These findings provide a basis for reformulating the role and function of artistic dissertations in the context of higher arts education in Indonesia.